English: English - I Dewa Ayu, Eka Pertiwi; Ni Komang, Ayu Agustini; Putu Gede, Wisnu Permana Kawisana (Politeknik Negeri Jember, 2025)
This community service activity is carried out through the Real Work – Community Empowerment Lecture Program (KKN-PMM) of Warmadewa University in 2025 with a focus on strengthening the digital marketing capacity of Micro, Small, and Medium Enterprises (MSMEs) in Sumerta Kaja Village, Denpasar. The background of this activity is the low use of digital technology by partner MSMEs, namely Pikat Project and Jangkep Art Studio, which still rely on conventional promotional strategies. The methods used are a participatory approach through socialization, training in creating and managing Google Business Profiles, digital content optimization assistance, and cross-platform integration with social media and marketplaces. The results of the activity show that there is an increase in digital literacy, optimization of business visibility, and the strengthening of a sustainable digital marketing ecosystem. However, the limited training time and lack of mastery of advanced technical aspects, such as local SEO and creative content strategy, are challenges that need to be considered in the next program. Practically, this activity proves that capacity-building-based interventions are able to increase the competitiveness of village MSMEs through the use of digital technology. Meanwhile, from the academic side, this activity contributes to the MSME digital literacy literature by emphasizing the importance of technical, cognitive, managerial, and social dimensions in the digital transformation process